2022
DOI: 10.1021/acsomega.2c06177
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Novel Bis-imino and Bis-amino Curcuminoids for Evaluation of Their Anticancer and Antibacterial Activity

Abstract: A new set of curcumin analogues with a Schiff base moiety were synthesized from a bis-aldehyde derivative of hydroxybenzylidene cyclohexanone and various alicyclic and aromatic amines. The single crystals of compound 2 (bis-aldehyde), compound 3b (bis-cyclohexylimino derivative), and compound 3c (bis-1-imino piperidyl derivative) were developed. The said bis-imino and bis-amino curcuminoids were tested for anticancer activity against MCF-7 utilizing the conventional MTT assay. These Schiff bases had significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…Curcumin has received great attention over the last two decades as an anticancer agent. [17,[128][129][130] Recent literature revealed that DHPMs exhibited a broad spectrum of anticancer activity. [131,132] The curcumin-based 3,4-DHPMs displayed [72] potential cytotoxicity against Hep-G2 (human hepatocarcinoma), human colorectal carcinoma cell line (HCT-116, human colon carcinoma), and human lung carcinoma cell lines (QG-56).…”
Section: Anticancer Propertiesmentioning
confidence: 99%
“…Curcumin has received great attention over the last two decades as an anticancer agent. [17,[128][129][130] Recent literature revealed that DHPMs exhibited a broad spectrum of anticancer activity. [131,132] The curcumin-based 3,4-DHPMs displayed [72] potential cytotoxicity against Hep-G2 (human hepatocarcinoma), human colorectal carcinoma cell line (HCT-116, human colon carcinoma), and human lung carcinoma cell lines (QG-56).…”
Section: Anticancer Propertiesmentioning
confidence: 99%
“…The currently employed methods for breast cancer treatment include prophylactic mastectomy, chemotherapy, radiotherapy, medicines, and gene therapy [ [4] , [5] , [6] ]. However, these methods of treatments are usually associated with pain and considered expensive particularly in countries with low- and middle-income rates [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%